Expression of betacatenin in carcinoma in pleomorphic adenoma, pleomorphic adenoma and normal salivary gland: an immunohistochemical study - do Prado, Renata Falchete; Consolaro, Alberto; Taveira, Luís Antônio de Assis (My University, 2006)
OBJECTIVES: Pleomorphic adenomas are the most frequent type of epithelial salivary gland neoplasms, and their malignant counterpart, the carcinoma in pleomorphic adenomas, is much less common. Beta-catenin is a cell adhesion molecule associated with the invasion and metastasis of carcinomas of the head and neck, esophagus. The objective of this study was to detect the expression of beta-catenin in pleomorphic adenomas, carcinomas in pleomorphic adenomas and normal salivary glands to discuss its role in the development of these two lesions. STUDY DESIGN: The expression of beta-catenin (BD Transduction Laboratories) was analyzed by immunohistochemistry in formalin-fixed, paraffin embedded specimens by the avidin-biotin-peroxidase complex method in 16 pleomorphic adenomas (12 from minor salivary glands), 3 carcinomas in pleomorphic adenomas (all from palate) and 10 normal salivary glands as control group (5 from major and 5 from minor salivary glands). RESULTS: All cases of glands, adenomas and carcinomas in pleomorphic adenomas have membranous and cytoplasmic immunostaining. Nuclear beta-catenin immunostaining was not observed. The antibody presented a fine granular arrangement in the cytoplasm and cellular membrane of duct and acinic cells. Higher beta-catenin index rates were seen mainly in salivary gland ducts and in ductal structures in the adenomas and carcinomas in pleomorphic adenomas. There was protein loss in pleomorphic adenomas and cytoplasmic accumulation in carcinoma in pleomorphic adenomas. CONCLUSIONS: The present study showed participation of the loss of beta-catenin adhesion molecule in the development of pleomorphic adenoma, and that the cytoplasmic accumulation of the molecule takes part in the malignant transformation of the pleomorphic adenoma into carcinoma in pleomorphic adenoma.
Keywords: beta catenin; adult; aged; biosynthesis; carcinoma; child; female; human; immunohistochemistry; male; metabolism; middle aged; multiple cancer; pleomorphic adenoma; salivary gland; salivary gland tumor; Adenoma, Pleomorphic; Adult; Aged; beta Catenin; Carcinoma; Child; Female; Humans; Immunohistochemistry; Male; Middle Aged; Neoplasms, Multiple Primary; Salivary Gland Neoplasms; Salivary Glands